Feeding and physiological energetics of the littoral Tellinoidea of Dublin Bay - DANIELS, LINDA CHARLOTTE (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2018)
The littoral Tellinoids, marine bivalve clams, are an important component of the Dublin Bay ecosystem, comprising a third of benthic macrofaunal biomass and providing a key conduit in the flow of energy through the system. UNESCO Dublin Bay Biosphere is a site of high ecological value. The purpose of this investigation is to examine the feeding mode and physiological energetics of the littoral Tellinoidea (Blainville, 1814) of Dublin Bay, in order to better understand resource partitioning and niche division within this superfamily. The superfamily of the Tellinoidea all share a similar body plan. The five species of Tellinoids examined were Scrobicularia plana, Macomangulus tenuis, Limecola balthica, Fabulina fabula and Donax vittatus. Suspensivores and deposivores have distinct roles in nutrient cycles and partition resources differently. Suspension feeders link benthic and pelagic systems and compete for the same resources, while deposit feeders recycle nutrients and partition resources. Distribution, abundance and biomass of all macrobenthos was recorded in the field. For the first time, palp to gill area was employed to determine the feeding mode of five members of this superfamily. Diet composition and suspended particle capture efficiencies were established. Feeding variables, Scope for Growth (SFG) and Gut Passage Time (GPT) were determined. It was found that the Tellinoidea comprise 32% of benthic biomass of the areas investigated. There were two distinct environmental biotopes in the Dublin Bay littoral zone area examined, distinguished by silt, redox potential discontinuity (RPD), salinity and biota. M. tenuis was the most widespread Tellinoid, and the only species found in both environments. The type of feeding undertaken by bivalves, deposit or suspension, defines their impact on the system. D. vittatus and M. tenuis were classified as suspensivores, L. balthica was classified as deposivorous, and F. fabula and S. plana as using both feeding modes. Palp:gill area ratios of L. balthica were highest, and significantly higher than those of S. plana. M. tenuis and F. fabula’s differences in palp:gill area ratios were confirmed using a novel photographic analysis technique developed. Picoplankton < 2 μm formed a large part of the diet of the Tellinoids examined, especially for D. vittatus. Foraminifera were recorded in the diet of L. balthica, a first record. Spheroidal plankton constituted approximately half the diet of the Tellinoid species examined, more in D. vittatus, and less in M. tenuis. Particles > 4 μm were more efficiently captured from a suspension of multiple particle sizes, and no distinctive peaks in capture efficiency were noted. The Tellinoid species tested here did not partition niches according to particle sizes captured. SFG and GPT highlighted energetic efficiency differences, with D. vittatus exhibiting negative SFG under the test conditions. M. tenuis, the most abundant and widespread Tellinoid, showed the greatest potential in terms of competitive ability, while D. vittatus showed the least. L. balthica and S. plana are found in the same environments, sharing a similar feeding mode and capturing plankton (prey) size ranges in experimental conditions with similar efficiency, but with S. plana ingesting smaller particles (< 2 μm) in its diet. F. fabula and D. vittatus were also found in similar environments to each other, mostly near the Low Water Mark in clean sand, and both were subject to potential increasing competition with M. tenuis towards the mid-shore. M. tenuis is found in all environments, it has high SFG, and is much more abundant where F. fabula and D. vittatus also occur. The outcomes of the work, elucidating feeding mode and feeding energetics of Tellinoids, can be applied to future network analyses of Dublin Bay’s ecosystem, providing a basis for evidence-based conservation objectives.
APPROVED